Humic substances from sediments of Lobos Pond (Argentina). Isolation, characterization and limnological implications - Choconi, Roberto Gustavo; Ghini, Alberto Antonio; Conzonno, Victor Hugo; Cirelli, Alicia Fernández (Eclética Química, 2012)
Humic substances (HS) were isolated from the sediments of Lobos Pond (Argentina) using mild conditions to preserve their native structure. The HS (humic and fulvic acids) were characterized by means of elemental analysis and FTIR spectroscopy. Also a by-product obtained during fulvic acids (FA) fractionation (an amorphous white solid residue) was analyzed. Results revealed possible interactions between FA and inorganic-organic substances that may have implications referring to bioavailability. Other limnological implications, such as autochtonous origin of HS linked with the hydrology, and change of pH during stormy weather that affects HS interactions, are discussed.